Analysis of thermodynamic parameters of glass forming polymeric melts - Mishra R.K.; Dubey K.S. (My University, 2025)
The temperature dependence of the Gibbs free energy difference (ΔG), enthalpy difference (ΔH) and entropy difference (ΔS) between the undercooled melt and the corresponding equilibrium solid has been analysed for glass forming polymeric materials by calculating ΔG, ΔH and ΔS within the framework of the hole theory of liquids. The study is made for nine samples of glass forming polymeric melts; polypropylene oxide (PPO), polyamid-6 (PA-6), polytetramethylene oxide (PTMO), polyethylene oxide (PEO), polystyrene (PS), polypropylene (PP), polyethylene (PE), polyethylene terephthalate (PET) and polybutadiene (PB) and three simple organic liquids: tri-α-naphthyl benzene (tri-α-NB), o-terphenyl (o-ter) and phenyl salicylate (salol) in the entire temperature range Tm (melting temperature) to Tg (glass transition temperature). The ideal glass transition temperature (TK) and the residual entropy (ΔSR) of these samples have also been studied due to their important role in the study of the glass forming ability of materials.